Fosfomycin as a potential treatment for neonatal sepsis An open label randomised clinical trial evaluating safety and pharmacokinetics - Obiero, C; Williams, P; Murunga, S; Thitiri, J; Omollo, R; Walker, AS; Egondi, T; Nyoake, B; Correia, E; Kane, Z; Gastine, S; Kipper, K; et al. (BMJ Publishing Group, 2022)
Objective To assess pharmacokinetics and changes to sodium levels in addition to adverse events (AEs) associated with fosfomycin among neonates with clinical sepsis.